Māori Affairs and Public Policy - Sullivan, Ann (New Zealand government and politics, 2003)
Keywords: Elections -- New Zealand; New Zealand -- Politics and government -- 1972-; New Zealand Parliament -- Elections, 2002; Political parties -- New Zealand; Proportional representation -- New Zealand; Representative government and representation -- New Zealand

Mana Māori Motuhake: The State of the Māori Nation - Durie, Mason (New Zealand government and politics, 2003)
Keywords: Elections -- New Zealand; New Zealand -- Politics and government -- 1972-; New Zealand Parliament -- Elections, 2002; Political parties -- New Zealand; Proportional representation -- New Zealand; Representative government and representation -- New Zealand

Māori Representation in Local Government - Sullivan, Ann (Local government and the Treaty of Waitangi, 2003)
Keywords: Kāwanatanga; Local government -- New Zealand; Māori; Māori (New Zealand people) -- Government relations; New Zealand Resource Management Act 1991; Resource Management Act 1991 (New Zealand); Tiriti o Waitangi; Treaty of Waitangi (1840 February 6)

Local Government and the Waitangi Tribunal - Hemi, Murray (Local government and the Treaty of Waitangi, 2003)
Keywords: Kāwanatanga; Local government -- New Zealand; Māori; Māori (New Zealand people) -- Government relations; New Zealand Resource Management Act 1991; Resource Management Act 1991 (New Zealand); Tiriti o Waitangi; Treaty of Waitangi (1840 February 6)

Appendix to Chapter 2: Kaitiakitanga: A Commentary on the Resource Management Act - Tutua-Nathan, Tikitu (Local government and the Treaty of Waitangi, 2003)
Keywords: Kāwanatanga; Local government -- New Zealand; Māori; Māori (New Zealand people) -- Government relations; New Zealand Resource Management Act 1991; Resource Management Act 1991 (New Zealand); Tiriti o Waitangi; Treaty of Waitangi (1840 February 6)

Resource Management, Local Government, and the Treaty of Waitangi - Love, Morris Te Whiti (Local government and the Treaty of Waitangi, 2003)
Keywords: Kāwanatanga; Local government -- New Zealand; Māori; Māori (New Zealand people) -- Government relations; New Zealand Resource Management Act 1991; Resource Management Act 1991 (New Zealand); Tiriti o Waitangi; Treaty of Waitangi (1840 February 6)

Philosophical Foundations of Maori-Crown Relations in the Twenty First Century: Biculturalism or Self-Determination - O'Sullivan, Dominic (APSA, 2003)
This paper demonstrates that the philosophical premises underlying biculturalism and self-determination lead to different conclusions about where power properly resides with respect to Crown/Maori relations in New Zealand. It is argued that biculturalism is not the panacea for the realisation of legitimate Maori aspirations that has been assumed by both Maori and Pakeha policy elites over the past twenty years because it makes assumptions about power relationships which limit greater degrees of Maori autonomy ' one step towards self-determination is permitted, but the next prevented. Biculturalism can not realise greater autonomy because it is concerned primarily with relationships among people in institutional settings and within and among bureaucratic institutions. Therefore it is less likely to meet Maori aspirations than self-determination which is concerned with creating, to the greatest extent possible, independence and autonomy for groups, not necessarily in isolation from wider society, but certainly apart from controls and regulations imposed from outside the would be self-determining community. Self-determination locates power, at least to some extent, within traditional Maori social units, while biculturalism, although assuming a sharing of power, inevitably gives Maori the status of junior partner in a project designed to modify state institutions to make them more responsive to Maori interests. While in itself this is advantageous to Maori, biculturalism is not a substitute for the affirmation of traditional social structures as the central point in a Maori quest for greater independence from an historically intrusive state.
Keywords: Biculturalism; Indigenous Politics; Maori; New Zealand Politics; Self-Determination

A fire in your belly: Māori leaders speak - Diamond, Paul; O'Regan, Tipene; Winiata, Whatarangi; Tawhiwhirangi, Iritana; Mead, Hirini Moko; Sharples, Pita (Huia, 2003)
Keywords: iwi; leadership; treaty settlements

The balance destroyed: the consequences for Māori women of the colonisation of Tikanga Māori - Mikaere, Annabel (Published Jointly by the International Research Institute for Māori and Indigenous Education and Ani Mikaere, 2003)
Keywords: colonisation; crown law; european influences; mana wāhine; sexism; social conditions; social life and customs; wāhine māori

The Politics of Māori Image and Design - Jahnke, Robert; Jahnke, Huia Tomlins (He Pukenga Korero: a journal of Māori studies, 2003)
Keywords: cultural appropriation; indigenous data sovereignty; intellectual property; mātauranga māori; rangatiratanga; social life and customs; tāngata whenua

Panic on the beach - Jackson, Moana (Mana Magazine, 2003)
Keywords: foreshore and seabed act 2004; racism

The changing images of nineteenth century Māori society: from tribes to nation - Henare, Manuka Arnold (2003)
Keywords: colonisation; he whakaputanga; history; self-determination; thesis; tino rangatiratanga; tiriti o waitangi/treaty of waitangi

Backgrounding the Paeroa Declaration - Jackson, Moana (2003)
Keywords: foreshore and seabed act 2004; hapū; iwi; protest

Perceptions, conceptions and realities : a study of the tribe in Maori society in the twentieth century - Maaka, Roger (2003)
This thesis aims to provide an understanding of the nature of tribes and tribalisation in Maori society that is not readily available from secondary sources. It is an attempt to move out of the fog created by the intense politicisation that surrounds definitions and perceptions of the tribe, which in turn have created a bewildering maze of issues and demands. For example social change and development among Maori - and by implication the tribe - has been characterised variously as renaissance (Durie 1998), neo tribalism (Rata 2000), the reification of culture (Hansen 1989, van Meijl 1996), and political struggle (Walker 1990). These conceptualisations have not taken into account the fact that the tribe as the fundamental social organisation of Maori society and the tribe as the fundamental essence of Maori identity diverged as the twentieth century progressed. This thesis offers an alternative view of social change based on a study of the changing perceptions of the tribe throughout the twentieth century. The underlying premise is that perceptions of the tribe evolved according to a range of endogenous and exogenous social and political influences. This position is juxtaposed against the proposition that the tribe is, and can be understood simply from observation of communities, past and present. Throughout the twentieth century the tribe's status as the primary organising force changed. In the early stages of the century the tribe was the primary, as well as the fundamental, form of Maori social organisation and identity. As the century progressed and Maori became progressively integrated into the wider New Zealand society, alternative forms of association became available to Maori. The tribe remained the fundamental source of identity: it was, however, no longer the primary social grouping for many Maori. That is, the majority of Maori claimed affiliation to a tribe but did not live and work in a tribal context. It is argued in this thesis that existing perceptions of the tribe have taken into account only the former, that the tribe was the fundamental expression of Maori kinship and identity and have ignored the reality that the tribe was no longer the most common and influential organizing force of Maori social organisation. It is also argued that these perceptions have been formed through three sets of interacting agency: Maori, government and scholarship. Maori understandings of the tribe were primarily sourced in life circumstances, in understandings of a society with a range of kinship inter and intra relationships that are encapsulated in traditional forms of association, namely iwi, whanau and hapu. However, what was not widely understood is that the influence of government through its Maori policies and its fostering of academic scholarship through research publications and advocacy, have had formative, descriptive and prescriptive influences on the tribe. This ongoing process has resulted in an interplay of categorical definitions and adjustments and strategic developments. Understanding conceptions and perceptions of the tribe are very pertinent, not only to Maori, but also to New Zealand as a whole. The tribe dominates notions of Maori identity as well as Maori political and social organisation. Since Maori constitute 15% of the total population of New Zealand, any research that assists in understanding the tribe assists in understanding New Zealand society. The tribe is also an integral part of Treaty-centred politics, and, therefore, a key plank of nation-building within New Zealand. The tribe as an autonomous polity had became a contested site in the late twentieth century, to the extent that definitional disputes disrupted and threatened to derail attempts by government and tribal leaders to arrive at Treaty settlements. Understandings and misunderstandings of the tribe therefore have ramifications for race relations, and the Maori quest for self-determination, as well as for republicanism, constitutionalism and democracy as understood and practiced in New Zealand. This thesis argues: 1. That perceptions and conceptions of the tribe were formed through the interlocking agencies of Maori, scholarship and government. 2. That the key to understanding the tribe and tribalisation in Maori society in the twentieth century is the acceptance that the tribe as the basis of identity and the tribe as the basis community organisation diverged as the century progressed. 3. That tribal affiliation remained central to understandings of Maori identity in spite of major societal changes that they experienced during the twentieth century, 4. That in the latter part of the twentieth century that movement to revitalise the tribe developed into an ideology of retribalisation that successfully introduced a prescribed form of tribe, a development that changed the fundamental nature of tribes and tribalisation among Maori.
Keywords: identity; iwi; social organisation

The dynamics of ethnicity reporting: Māori in New Zealand : a discussion paper prepared for Te Puni Kōkiri / by Tahu Kukutai. - Kukutai, Tahu (Te Puni Kōkiri, 2003)
Keywords: demographic aspects; ethnic identity; identity; statistics